A Covid-19 Social Assistance Corruption Case On Jakarta Globe News Articles: A Framing Analysis - Qadar, Ogy Adidaya; Merrita, Diah (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2023)
Political news is always related to framing which is used to find out the perspective or point of view used by journalists or mass media when selecting issues and writing news. The way journalists or media writes the news and shows their point of view will determine whether or not the media favors certain groups. This study will examine how the Jakarta Globe frames the news regarding the corruption case of the Covid-19 social assistance fund carried out by the former of Social Minister, Juliari Peter Batubara. The data used in this study are three news published by Jakarta Globe on December 6, 2020 which the same day with the former of Social Minister Juliari Peter Batubara surrendered himself to the KPK. The method used in this study is a qualitative approach using framing analysis from Zhongdang Pan and Gerald M Kosicki. Framing analysis from Zhongdang Pan and Gerald M. Kosicki focuses on four structures, namely syntax, script, thematic, and rhetorical. The conclusion is the Jakarta Globe is not neutral in the writing of corruption cases carried out by the former of Social Minister Juliari Peter Batubara in a very subtle way.